SERUM VITAMIN D3 LEVEL IN MIGRAINE PATIENTS- A HOSPITAL BASED CASE-CONTROL STUDY. - Panda, Sujata; Sahu, Sasmita; Bhoi, Sanghamitra; Kiro, Jyotsna; Pandey, Mamata; Panda, Bimal Krushna (Student’s Journal of Health Research Africa, 2023)
Introduction: The most prevalent type of headache is migraine and it typically presents with a unilateral, pulsatile severe headache lasting from 4 to 72 hours accompanied by nausea, photophobia, and transient neurological symptoms. Also, in recent years Vit D3 deficiency has emerged as a global public health problem amounting to about 30-80% of children and adults having Vit. D3 deficiency. The study was to be taken for the role of vitamin D3 in the severity of migraine patients. Materials and Methods: This case-control study was conducted in the Department of ENT and Biochemistry, VIMSAR Burla from January 2023 to June 2023. Age groups of 10 - 60 years of either sex (sample size 65 each) were examined clinically and the severity of migraine was evaluated by MIDAS Score and Biochemical estimation of serum vitamin D3 level was done by CLIA analyzer (Electra FA). Statistical analysis was performed with SPSS software version 21.0 (SPSS IBM corporation, Armonk. New York). The p-value < 0.05 was taken as statistically significant. Results: A total of 65 subjects each from case (clinically diagnosed cases of migraine patients) and control group were evaluated. In the present study, 21 males and 44 females were from the case and 22 males and 43 females were included in control groups. The mean age of males and females were (43.23± 2.3) and (32.58 ± 2.4) in case (42.23± 2.5) and (36.58 ± 2.6) were in control groups. Serum vitamin D3 level was lower in case groups (18.01 ng/mL) and in control, it was (34.09 ng/mL). The association of serum vitamin D3 concentration with case and control was highly significant (p<0.05). Conclusion: There was a significant deficiency of Vitamin D3 in migraine patients as compared to control where serum vitamin D3 levels were normal.